Unraveling the ecological landscape of mast cells in esophageal cancer through single-cell RNA sequencing - Zhang, Shengyi; Zhang, Xinyi; Xiahou, Zhikai; Zuo, Shunqing; Xue, Jialong; Zhang, Yi (Frontiers in Immunology, 2024)
Esophageal cancer (EC) is a formidable health issue due to its high aggressiveness and poor prognosis. Despite advancements in treatment modalities, the survival rate remains dismal, often attributed to late-stage diagnosis and resistance to therapy. Mast cells (MCs), tissue-resident immune cells, play a significant role in the tumor microenvironment (TME) and have been implicated in both tumor-promoting and tumor-suppressing activities. Recent developments in high-throughput single-cell RNA sequencing (scRNA-seq) have allowed for the detailed dissection of tumor heterogeneity and the complex interactions between cancer cells and their microenvironmental components. However, the application of scRNA-seq in understanding the immune landscape of EC remains limited. In this study, we employed high-throughput scRNA-seq to investigate the TME of EC, focusing on the role of MCs. We analyzed six samples from patients with EC, identifying 11 major cell types and highlighting the significant presence of MCs in pericarcinoma tissues. Further subclustering of 5,001 MCs revealed eight distinct subtypes, among which MCs with high SRSF7 expression showing a strong tumor preference and potential tumor-promoting characteristics. Our findings underscore the complex interactions within the TME and suggest that targeting MC subtypes, particularly through the EGFR signaling pathway, could offer new therapeutic avenues. This study provides a comprehensive immune map of EC and lays the groundwork for developing more effective treatment strategies.